Assess Role of Public Health Nursing Nutrition Label in Assessment and Interventions of Women - Hussain Abdulhadi Alsidran; Qasem Adel Alkhalifah; Mohammed Ahmed Alshayeb; Abdulmohsen Hussain Abdulmohsen Alabd Rab Ulridha; Ali Ibrahim Alsaleh; Maryam Ibrahim Omar Almulhim; Zahrah Mohammed Hussain Alkhalaf; Rouqayyah Mohammed Alkhalaf; Kawther Mohammed Al Khalaf; Sara Hassan Albeladi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Obesity and chronic diseases are strongly linked to dietary habits, with women, individuals in rural areas, and those from lower socioeconomic backgrounds being particularly vulnerable. Public Health Nurses (PHNs) providing home-visit services are uniquely positioned to address nutritional concerns among at-risk populations. However, limited research exists on the role of PHN interventions in improving nutrition knowledge, behaviors, and outcomes. Methods: This study utilized de-identified data from adult female clients receiving PHN home visits. Nutrition-related data were documented using the Omaha System, which categorizes client problems, interventions, and outcomes across domains. Nutrition Knowledge, Behavior, and Status (KBS) were rated on a Likert scale from 1 (least favorable) to 5 (most favorable). Data from 558 clients were analyzed to assess their nutrition profiles, interventions received, and outcomes. Statistical tests compared client characteristics and intervention types across different home-visit categories. Results: The sample comprised 558 women, with an average age of 26.1 years. Participants received an average of 6.5 visits over 189 days. Nutrition KBS scores indicated basic knowledge (3.4), inconsistent to usually appropriate behavior (3.7), and minimal signs or symptoms (4.3). Nutrition interventions ranged from 0 to 36 per client, averaging 7.3 interventions. Women receiving high-risk family visits had lower Nutrition KBS scores but received the most nutrition interventions, addressing dietary management, feeding procedures, and behavior modification. First-time parent visits prioritized breastfeeding-related interventions, while non-pregnancy-related visits received the fewest interventions overall. Conclusion: While PHN home-visiting programs effectively address various health concerns, nutrition is not consistently assessed or prioritized. This study emphasizes the need for enhanced strategies to improve nutrition KBS among home-visited women. Expanding intervention diversity, including multicomponent strategies and case management, could further optimize outcomes and reduce health disparities. Future research should explore targeted, evidence-based nutrition interventions in PHN practices.